2014
DOI: 10.1007/s00787-014-0623-y
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and emotional problems in moderately preterm children with low socioeconomic status: a population-based study

Abstract: Moderately preterm (MP) birth is associated with higher rates of behavioural and emotional problems. To determine the extent to which low socioeconomic status (SES) contributes to these higher rates, we assessed independent and joint effects of MP birth and low SES, overall and by gender. Dutch preventive child health care centres provided a population-based sample of 915 MP children (32-36 weeks gestation) and 543 term-born children, born in 2002/2003. In multivariable logistic regression analyses, we determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 45 publications
2
35
2
Order By: Relevance
“…We also found that sociodemographic factors were the only significant independent predictors of delayed social competence in LMPT infants. The additive effect of low SES has previously been reported in this population 25,26 and may represent a potential target for identifying LMPT children who may benefit from early intervention.…”
Section: Discussionmentioning
confidence: 93%
“…We also found that sociodemographic factors were the only significant independent predictors of delayed social competence in LMPT infants. The additive effect of low SES has previously been reported in this population 25,26 and may represent a potential target for identifying LMPT children who may benefit from early intervention.…”
Section: Discussionmentioning
confidence: 93%
“…Few studies have so far attempted to investigate in more detail individual factors that may place subgroups at higher risk of later morbidity. Such factors might include genetic factors, maternal morbidity during pregnancy, reason for early delivery, variation in early care or nutrition, and socio-economic or environmental factors [21,30,[76][77][78][79]. Now that ongoing morbidities have been defined, further work is needed to elucidate whether there are modifiable factors with respect to pre-pregnancy, antenatal, neonatal, or childhood care that might improve outcomes.…”
Section: Implications For Health Care Provisionmentioning
confidence: 99%
“…In turn, even moderate preterm (32–36 weeks) birth multiplies the independent risk of low SES on behavioral and emotional problems in children [66]. Thus, supporting healthy pregnancy outcomes represents a salient and early way to begin to dismantle inequalities and transform life.…”
Section: The Prism Of Socioeconomic Gradientmentioning
confidence: 99%